Poverty Vulnerability and Health Risk Action Path of Families of Rural Elderly With Chronic Diseases: Empirical Analysis of 1,852 Families in Central and Western China - Ma, Ying; Xiang, Qin; Yan, Chaoyang; Liao, Hui; Wang, Jing (Frontiers in Public Health, 2022)
Health poverty has become the most important cause of poverty and return to poverty. Understanding the health risk factors and action paths of poverty in families of rural elderly with chronic diseases is important to alleviate return to poverty because of illness. This study selected families with at least one elderly member (over 60 years old) with chronic diseases (sample size was 1,852 families) in two provinces and four counties in central and western China. The three-stage feasible generalized least square method was adopted, and the appropriate poverty line standard was selected to measure the poverty vulnerability index. A poverty vulnerability index ≥50% was considered to indicate vulnerability. The poverty vulnerability index and actual income status were combined to classify the samples. A structural equation model was established to explore the path of each health risk factor on the entire sample and various types of poverty vulnerabilities. The mean poverty vulnerability of 1,852 families was 0.5974 ± 0.25213, and among which, 1,170 households had a poverty vulnerability value ≥0.5, accounting for 63.17% of the entire sample. The incidence of poverty was higher among people with low vulnerability to poverty. Health shock was the direct cause of poverty for people with potential and avoidance poverty. The mediating roles of family and community significantly differed in various types of poverty vulnerability. The social and economic environment in rural areas should be enhanced in a diversified manner, and the income-generating ability of rural households should be improved based on actual local conditions. Moreover, the prevention and control of poverty vulnerabilities should be diversified and targeted. Policies implemented should be based on people and localities, the causes of poverty and returning to poverty, and the types of poverty vulnerabilities. The use efficiency of medical insurance should be further improved, and the responsibility of medical insurance targeted poverty alleviation must be clarified.